EKSPERIMENTASI MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE DAN TALKING STICK PADA MATERI BANGUN DATAR DITINJAU DARI KEMANDIRIAN BELAJAR SISWA SMP NEGERI KELAS VII Se-KABUPATEN PEMALANG TAHUN 2019/2020 - Julian Reza siwi; Ayu Eka Putri (Program Studi Manajemen Pendidikan Islam (MPI) Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2020)
The objectives of this study were to find out on the topic of two dimentional figure: (1) which was better between Example Non Example, talking stick or Direct learning that produce learning achievement; (2) which one had better learning achievement between students with high, medium or low categories of independency learning; (3) at each category of independency learning, which was better between Example Non Example, talking stick or Direct learning that produce learning achievement; and (4) at each model pembelajaran, which one had better learning achievement between students with high, medium or low categories of independency learning. This study was a quasi-experimental with 3´3 factorial design. The population was all of students in seventh grade of State Junior High School in Pemalang Regency on Academic Year 2019/2020. The samples were taken by using a stratified cluster random sampling technique. The samples was students in seventh grade of SMP Negeri 1 Randudongkal, Moga and Pulosari. The instrument of this study were independency learning questionnaire and learning achievement test. The questionnaire tryout included content validity, internal consistency and reliability, and the test tryout included content validity, difficulty level, discrimination power, and reliability. Before the experiment was done, the balance of prior knowledge was examined by using unbalanced one way anova test. The hypothesis test used unbalanced two ways anova. Test requirements included normality test used Lilliefors method and the homogeneity test used the Bartlett test. The results of the study were as follows: (1) the Example Non Example model produce the learning achievement better than the Talking Stick and direct learning, the Talking Stick model give the same learning achievement as the direct learning; (2) the high and medium categories of independency learning have the same learning achievement, and both category of independency learning have better learning achievement from low categories of independency learning; (3) at each categories of independency learning, the Example Non Example model produce the learning achievement better than the Talking Stick and direct learning, the Talking Stick give the same learning achievement as the direct learning; and (4) at each models, the high and medium categories of independency learning have the same learning achievement, and both of category of independency learning style have better learning achievement from low categories of independency learning.